2020
DOI: 10.1111/jcmm.15940
|View full text |Cite
|
Sign up to set email alerts
|

Dual impacts of lncRNA XIST and lncRNA SNHG5 on inflammatory reaction and apoptosis of endothelial cells via regulating miR‐155/CARHSP1 axis

Abstract: Considering the significance of lncRNA/miRNA axis in explaining atherosclerosis (AS) progression, this investigation was intended to clarify whether lncRNAs XIST/SNHG5 would regulate AS aetiology by sponging miR‐155, an AS‐promoting molecule. We altogether recruited 367 patients who were examined by coronary angiography, and meanwhile, human coronary artery endothelial cells (HCAECs) were purchased to establish cells models via ox‐LDL treatment. The study results indicated that lowly expressed XIST/SNHG5 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…SNHG5 participates in inflammatory response and cell apoptosis. It mainly regulates the abovementioned biological processes by promoting the molecule miR-155, which affects the release of a large number of inflammatory cytokines from endothelial cells, leading to the occurrence of cell apoptosis [ 51 ]. Our results found that SNHG5 is positively correlated with neutrophils and endothelial cells, suggesting that SNHG5 may play a role in the immune response of IDD through the above pathways.…”
Section: Discussionmentioning
confidence: 99%
“…SNHG5 participates in inflammatory response and cell apoptosis. It mainly regulates the abovementioned biological processes by promoting the molecule miR-155, which affects the release of a large number of inflammatory cytokines from endothelial cells, leading to the occurrence of cell apoptosis [ 51 ]. Our results found that SNHG5 is positively correlated with neutrophils and endothelial cells, suggesting that SNHG5 may play a role in the immune response of IDD through the above pathways.…”
Section: Discussionmentioning
confidence: 99%